2019
DOI: 10.3390/vetsci6040076
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatments and Management of A Case of Canine Melioidosis

Abstract: This communication presents a successful story of an attempt to treat and manage a case of canine melioidosis, a severe tropical disease caused by Burkholderia pseudomallei. A 10-year-old dog was trapped with barbed wires, causing an infected wound around its neck and back, which was later diagnosed as severe melioidosis. The dog was treated based on a modified human protocol. Intravenous meropenem injections (20 mg/kg twice daily) were given for 14 days to prevent death from sepsis prior to treatment with ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Anemia and leukocytosis have previously been reported in dogs with melioidosis [20] but not in our study. This difference can be attributed to the fact that the dogs in our study had asymptomatic infections, characterized by normal appetite and absence of clinical signs.…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…Anemia and leukocytosis have previously been reported in dogs with melioidosis [20] but not in our study. This difference can be attributed to the fact that the dogs in our study had asymptomatic infections, characterized by normal appetite and absence of clinical signs.…”
Section: Discussioncontrasting
confidence: 66%
“…According to the results of this study, approximately 6% of the tested dogs showed seropositivity for B. pseudomallei. It is worth noting that canine melioidosis has been documented in only three articles, encompassing a total of five dogs, and two of these studies (involving two dogs) featured canine cases from Thailand [20][21][22]. However, PLT may play an important role in B. pseudomallei infection because thrombocytopenia has been previously reported in one dog with melioidosis [20] and in 31% of human patients [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations